Persepsi Konsumen terhadap Merek Minyak Goreng Sawit Kemasan di Indonesia - Putra, Romeyn Perdana; Purbawa, Yudha; Bakti, I Gede Mahatma Yuda; Astrini, Nidya J.; Purba, Helena Juliani; Sumaedi, Sik; Fahmi, Diah Arina (National Research and Innovation Agency, 2024)
Palm cooking oil (MGS) is an essential and vital staple affecting consumers' daily spending. The COVID-19 pandemic triggered a shortage of cooking oil in the Indonesian market around December 2021 until mid-2022. It can affect consumers' perceptions when purchasing MGS brands. This study aims to analyze consumer preferences for MGS brands in Indonesia. Specifically, it examines brand awareness, top-of-mind brands, most purchased brands, brand selection considerations, brand loyalty, and brand switching to other MGS brands. This study focuses solely on packaged MGS brands. The study used a survey method through an online questionnaire. Of the 707 respondents who completed the questionnaire, only 537 met the sample criteria for further analysis. The results showed that consumers perceive Bimoli as the leading MGS brand regarding brand awareness, top of mind, and top purchase. Other MGS brands frequently appearing in the top group include Sania, Sunco, Filma, and Tropical. The study also found that there are two primary considerations for consumers when choosing an MGS brand: (1) product factors (quality, health, clarity) and (2) sacrifice factors (price and accessibility). Furthermore, the study revealed that most MGS consumers are less loyal to a specific brand and are willing to switch to other brands.